Long-term outcomes after unilateral salpingo-oophorectomy: A registry-based retrospective cohort study. - Huan Yi; Naiqi Zhang; Jan Sundquist; Kristina Sundquist; Xiangqin Zheng; Jianguang Ji (PLoS Medicine)
Background Opportunistic bilateral salpingo-oophorectomy (BSO) is recommended in women who have undergone a hysterectomy due to gynecological carcinomas and/or in women with genetic indications, especially for women who do not intend to conceive. However, there is ongoing debate about whether BSO should be recommended in premenopausal women, due to the early cessation of estradiol because of BSO which is linked to several health concerns, including coronary artery disease (CAD) and osteoporosis. This study aims to explore whether ovarian cancer can be prevented by unilateral salpingo-oophorectomy (USO) while not affecting the long-term risk of CAD and osteoporosis. Methods and findings By accessing the Swedish national registries, this retrospective cohort study included 42,306 women who underwent USO between 1993 and 2018 before the age of 50 years. These women were randomly matched with 211,530 women who had not undergone USO using a propensity score matching approach to ensure comparability between the groups. Follow-up started on the date of USO operation and continued until the earliest occurrence of the following events: diagnosis of specific outcomes of interest, death from any cause, or the end of the study period (31st December 2018). Cox regression models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) of overall and histology-specific ovarian cancer, CAD, and osteoporosis associated with USO. After a median follow-up of 13 years, our analyses revealed that USO was not associated with subsequent risk of CAD (HR = 1.02, 95% CI [0.95, 1.09]) and osteoporosis (HR = 1.06, 95% CI [0.98, 1.16]). However, USO was significantly associated with a reduced risk of high-grade serous ovarian carcinoma (HR = 0.64, 95% CI [0.45, 0.92]). No differences were found when the analyses were stratified by hysterectomy. The main limitation of the study was that some confounding factors, such as BRCA1/2 pathological mutant status, were not available in our database. Conclusions Our study suggests that USO reduces the risk of HGSCs but was not associated with CAD or osteoporosis after a median 13-year follow-up. These results suggest that USO may be a safer option than BSO for lowering ovarian cancer risk in premenopausal women, as it could avoid the negative health effects of early menopause.